White Spruce Seedling (Picea glauca) Discovered North of the Brooks Range Along Alaska's Dalton Highway - Elsner, Wendy K.; Jorgenson, Janet C. (ARCTIC, 2009)
A white spruce seedling, Picea glauca (Moench) Voss, was found at the northern edge of the Brooks Range in Alaska, more than 50 km north of the latitudinal tree line. The seedling, 19 cm tall and about nine years old, was growing at the side of the Dalton Highway to Prudhoe Bay. It most likely sprouted from a seed transported across the Brooks Range on a vehicle and has survived on the well-drained gravel road berm, where site conditions are more favorable for germination and survival than in the surrounding tundra. This spruce has survived for about a decade under current climatic conditions. Even with a warming climate, natural seed dispersal is severely hampered by the rugged topographic barrier of the Brooks Range. Considering the amount of vehicle traffic on the Dalton Highway, however, it is likely that more pioneering spruce seedlings will turn up along this corridor. Once over the Brooks Range, a spruce population can potentially develop and expand. Un plant d’épinette blanche, Picea glauca (Moench) Voss, a été trouvé du côté nord de la chaîne de Brooks en Alaska, plus de 50 kilomètres au nord de la limite forestière latitudinale. Le plant de 19 centimètres de hauteur a environ neuf ans et pousse au bord de l’autoroute de Dalton, vers la baie Prudhoe. Il est vraisemblablement le fruit d’une graine transportée par un véhicule à travers la chaîne de Brooks. Il a survécu sur la berme de la route de gravier bien irriguée, où les conditions sont plus favorables à la germination et à la survie des graines que dans la toundra environnante. Cette épinette vit depuis une dizaine d’années dans les conditions climatiques actuelles. Malgré le réchauffement climatique, la dispersion naturelle des graines est gravement entravée par la barrière topographique accidentée de la chaîne de Brooks. Cependant, compte tenu de l’intensité de la circulation routière sur l’autoroute de Dalton, il est fort possible que d’autres plants d’épinettes poussent le long de ce corridor. Une fois de l’autre côté de la chaîne de Brooks, ...